2013
DOI: 10.1089/zeb.2012.0805
|View full text |Cite
|
Sign up to set email alerts
|

In VitroNeutralization of Viral Hemorrhagic Septicemia Virus by Plasma from Immunized Zebrafish

Abstract: We studied humoral long-term adaptive viral neutralization responses in zebrafish (Danio rerio), an increasingly useful vertebrate model for viral diseases actually limited by the absence of standardized anti-zebrafish immunoglobulin M (IgM) antibodies. We established an alternative method, similar to those used in other fish, to achieve a first estimation of zebrafish anti-viral antibody-like responses. We used the viral hemorrhagic septicemia virus (VHSV) model because, although protection after this non-nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
11
0
2
Order By: Relevance
“…The expression and antiviral activity of IFNs and Mxa have been extensively described in zebrafish. Viral hemorrhagic septicemia virus (VHSV)-infected zebrafish showed an increase in ifna , ifnb , and mxa gene expression, reaching a maximum after 72 h ( 47 ). In our case, we did not detect significant changes in the expression of ifnphi1-3 genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression and antiviral activity of IFNs and Mxa have been extensively described in zebrafish. Viral hemorrhagic septicemia virus (VHSV)-infected zebrafish showed an increase in ifna , ifnb , and mxa gene expression, reaching a maximum after 72 h ( 47 ). In our case, we did not detect significant changes in the expression of ifnphi1-3 genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the small amount of serum obtainable from small fish such as zebrafish precludes such assays. Studies in zebrafish infected with rhabdovirus, such as viral hemorrhagic septicemia virus (VHSV), have shown that plasma from surviving zebrafish has a neutralizing activity in fish cells in vitro and that the neutralization correlated with the level of in vivo protection ( 47 ). Synergy between antibodies, cytokines, and phagocytes against intracellular pathogen appears to be critical for clearance of an infection.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain concentrated VHSV for neutralizing assays, supernatants were centrifuged at 60.000 g for 180 min at 4°C, and pellets were frozen at -70°C until use. VHSV was titrated by the focus forming units (ffu) assay [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been well demonstrated that teleost B cells proliferate and secrete pathogen-specific antibody (Zhang et al, 2010; Xu et al, 2013; Cain et al, 2002; Castro et al, 2013; Chinchilla et al, 2013), the importance of humoral immunity in controlling infections in zebrafish is unclear. For example, zebrafish B cells appear to have little to no role in the response against Edwardsiella tarda (Yang et al, 2013).…”
Section: The Function Of Apcs In Zebrafishmentioning
confidence: 99%